Avoiding common breaks in sterile technique. Issue 5 (27th September 2015) - D'Alesandro, MaryAnn
Abstract : Recognizing breaks in sterile technique includes properly delivering solutions to the sterile field and setting up sterile supplies. Each step decreases patients' risk of infection.